The concept of monotheism (Tawhid) in the Jewish doctrines - Al-Tashlan, Shorouq Mohammed (Journal of Islamic Sciences, 2023)
This study presents findings on Jewish inclinations toward monotheistic (Tawhid) concepts through an extrapolation of Jewish doctrines, an exploration of Jewish trends regarding the divine entity and attitudes (Sifāt), and a thorough examination of the underlying reasons for these attitudes. The methodology employed in this research was descriptive and exploratory in nature.The study was structured into two distinct chapters. The first chapter was dedicated to an investigation of the Jewish curriculum pertaining to the study of the divine entity. The second chapter focused on the Jewish curriculum related to the study of divine issues. A key discovery in this research pertains to the Jewish perspective on issues related to the divine entity, which can be classified into three discernible trends: the proof trend, the stereotypical analogy trend, and the interpretation trend. Upon closer examination of these trends, it becomes apparent that the proof trend intersects with the stereotypical trend when it substantiates divine qualities that are harmonious with human attributes in terms of their nomenclature. However, the two trends are differentiated by a correct understanding of the divine entity. Conversely, the emergence of the stereotypical trend poses a challenge insofar as it implies a correspondence between divine attributes and human characteristics based solely on shared names.
Keywords: Jews; approaches; attributes; divine; impeccable; interpretive; anthropomorphic